2016
DOI: 10.1002/asia.201600771
|View full text |Cite
|
Sign up to set email alerts
|

Room‐Temperature and Aqueous‐Phase Synthesis of Plasmonic Molybdenum Oxide Nanoparticles for Visible‐Light‐Enhanced Hydrogen Generation

Abstract: A straightforward aqueous synthesis of MoO3-x nanoparticles at room temperature was developed by using (NH4 )6 Mo7 O24 ⋅4 H2 O and MoCl5 as precursors in the absence of reductants, inert gas, and organic solvents. SEM and TEM images indicate the as-prepared products are nanoparticles with diameters of 90-180 nm. The diffuse reflectance UV-visible-near-IR spectra of the samples indicate localized surface plasmon resonance (LSPR) properties generated by the introduction of oxygen vacancies. Owing to its strong p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 43 publications
2
34
0
Order By: Relevance
“…[14] As for the XRD pattern of MoO 3Àx nanodots, only ab read-shape peak can be found, suggesting that the as-obtained product is amorphous. [15] The above result is in agreement with the HRTEM images. Furthermore, Ramanspectra were utilized to character-ize the phase of the sample.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…[14] As for the XRD pattern of MoO 3Àx nanodots, only ab read-shape peak can be found, suggesting that the as-obtained product is amorphous. [15] The above result is in agreement with the HRTEM images. Furthermore, Ramanspectra were utilized to character-ize the phase of the sample.…”
supporting
confidence: 88%
“…05‐0508) . As for the XRD pattern of MoO 3− x nanodots, only a bread‐shape peak can be found, suggesting that the as‐obtained product is amorphous . The above result is in agreement with the HRTEM images.…”
Section: Figurementioning
confidence: 98%
“…After that, they prepared Pd/MoO 3−x hybrid and it exhibited great plasmon-enhanced hydrolysis of NH 3 BH 3 [72]. The MoO 3−x nanoparticles were fabricated, and the enhanced LSPR property generated by the introduction of oxygen vacancies [73]. Further, they explored the effect of reduction temperature to MoO 3 , and MoO 3−x -200 • C (H 2 reduction temperature) showed a higher dehydrogenation activity [74].…”
Section: Ammonia Borane Dehydrogenationmentioning
confidence: 99%
“…The Mo doping provided a small pore diameter leading to an enhanced specific surface area (BET area changed from 13.2 to 62.1 m 2 /g), which is contributed to enhance hydrolysis of NH 3 BH 3 [75]. The stability of existing MoO 3 -based catalyst is not desirable due to relatively short test time (60-70 min) [72][73][74][75].…”
Section: Ammonia Borane Dehydrogenationmentioning
confidence: 99%
“…It is well known that an amorphous structure can provide ample active sites, which can be used to further enhance catalytic activity. An example is the work by Shi et al., who demonstrated that the plasmon absorption of amorphous MoO 3− x nanoparticles can be obtained by using two Mo precursors with two different valence states . With visible‐light illumination, the plasmonic MoO 3− x nanoparticles showed tremendously enhanced H 2 evolution from NH 3 BH 3 solutions compared to the same experiment performed in the dark.…”
Section: Amorphous Materials With Lsprmentioning
confidence: 99%